2020
DOI: 10.1111/iwj.13330
|View full text |Cite
|
Sign up to set email alerts
|

Surgical site infection following operative treatment of open fracture: Incidence and prognostic risk factors

Abstract: Considering the high incidence of postoperative complications of open fracture, management of this injury is an intractable challenge for orthopaedist, and surgical site infection (SSI) is the devastate one. Screening for high‐risk patients and target them with appropriate interventions is important in clinical practice. The aim of this study was to identify modifiable factors that were associated with SSI following operative treatment of open fractures. This retrospective, multicentre study was conducted at t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 21 publications
0
13
0
Order By: Relevance
“…The results of univariate and multivariate analyses performed by Hu et al. 24 showed that the fracture type, operative duration of >122 minutes, anesthesia time of >130 minutes, intraoperative body temperature of <36.4°C, GLU concentration of >100 mg/dL, PLT count of <288 × 10 9 , and WBC count of >9.4 × 10 9 were independent risk factors for wound infection after surgical treatment of open fractures. In vitro experiments have shown that PLT interactions enhance the phagocytic capacity of neutrophils against various bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…The results of univariate and multivariate analyses performed by Hu et al. 24 showed that the fracture type, operative duration of >122 minutes, anesthesia time of >130 minutes, intraoperative body temperature of <36.4°C, GLU concentration of >100 mg/dL, PLT count of <288 × 10 9 , and WBC count of >9.4 × 10 9 were independent risk factors for wound infection after surgical treatment of open fractures. In vitro experiments have shown that PLT interactions enhance the phagocytic capacity of neutrophils against various bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…77 A retrospective, multicentre study of 2692 patients with open fractures has reported a 18.6% overall incidence of surgical site infection, with 1.6% being deep infection. 121 Furthermore, they identified several risk factors associated with wound infection, including fracture type, increased operative duration (>122 min), increased anaesthesia time (>130 min), reduced intra-operative body temperature (<36.4 C), high blood glucose (>100 mg/dL), low blood platelets (<288 Â 10 9 ), and high white blood cells (9.4 Â 10 9 ). 121 There are no universal definitions for superficial and deep infection following open fracture injuries, however, these can be adjusted from the Centre's for Disease Control original definitions for surgical site infections.…”
Section: Infectionmentioning
confidence: 99%
“…121 Furthermore, they identified several risk factors associated with wound infection, including fracture type, increased operative duration (>122 min), increased anaesthesia time (>130 min), reduced intra-operative body temperature (<36.4 C), high blood glucose (>100 mg/dL), low blood platelets (<288 Â 10 9 ), and high white blood cells (9.4 Â 10 9 ). 121 There are no universal definitions for superficial and deep infection following open fracture injuries, however, these can be adjusted from the Centre's for Disease Control original definitions for surgical site infections. 122 A superficial infection can be defined as any infection which involves the skin and subcutaneous tissue (Fig.…”
Section: Infectionmentioning
confidence: 99%
“…Published studies had confirmed that age, body mass index (BMI), greater index of comorbidities, hypoalbuminemia, surgical duration, increased duration of anesthesia, current smoking, and elevated fasting blood glucose level were the risk factors of SSI for hip fracture patients [ 9 12 ]. However, most previous studies focused on hip fractures, while only a few studies focused on femoral neck fractures separately.…”
Section: Introductionmentioning
confidence: 99%